Reviving the Monroe Doctrine – Trump’s Campaign for Panama, Canada and Greenland - Petrović, Rajko (Napredak, 2025)
The research subject in this paper is the foreign policy of the newly-appointed US president Donald Trump in relation to the parts of the Western Hemisphere – primarily Panama, Canada and Greenland, openly claiming them for the United States of America. The starting hypothesis is that Donald Trump wants to revive the Monroe Doctrine formulated as early as 1823 and stipulating that the United States should be the indisputable master of the Western Hemisphere. The research results show that, despite Donald Trump’s pompous announcements that he would expand the territory of his country during the first six months of his mandate, no significant steps were taken in that direction. In the research, the historical method, the analysis method and the case study method were applied.
Keywords: Donald Trump; United States of America; Monroe Doctrine; Western Hemisphere